Effects of a school-based substance use prevention program on students in Malaysia - Tan, Renee Huey Jing; Yee, Anne; Sulaiman, Ahmad Hatim; Said, Mas Ayu; Danaee, Mahmoud; Lua, Ahai Chang (University of Malaya Medical Centre, 2018)
Background: The rise in substance-use-related problems among Malaysian adolescents called for a study to assess the efficacy of an anti-drug educational program to improve the knowledge, attitude and perception (KAP) of Malaysian students regarding substance use. Methods: This study involved 573 students from four Malaysian Chinese schools in Malacca. Each student filled out a Likert-scale mandarin translated questionnaire (KAP-C) on substance use (Pre-test). Following an educational program on substance use, the KAP-C questionnaire was given again to the students, immediately following the program (PT 1), and after a month (PT 2) and two months (PT3) of the programme. Results: The students showed improvement in knowledge of the types of substance use in PT 1 (p<0.001), PT 2 (p<0.001) and PT 3 (p<0.001). The study also showed persistent changes in their attitude towards drug treatment strategies at two months following the program (p < 0.05). Changes were also noted in their attitudes towards harm reduction strategies. Perceptions towards the substance-related problems changed following the module (p=0.001), and remained even after two months (p<0.001). Conclusion: This module effectively changed the KAP of students on substance use.